Olive Leaf Extracts Protect Cardiomyocytes against 4-Hydroxynonenal-Induced Toxicity In Vitro: Comparison with Oleuropein, Hydroxytyrosol, and Quercetin - Bali, Elif Burcu; Ergin, Volkan; Rackova, Lucia; Bayraktar, Oğuz; Küçükboyacı, Nurgün; Karasu, Çimen (Planta Medica, 2014)
Olive (Olea europaea) leaf, an important traditional herbal medicine, displays cardioprotection that may be related to the cellular redox modulating effects of its polyphenolic constituents. This study was undertaken to investigate the protective effect of the ethanolic and methanolic extracts of olive leaves compared to the effects of oleuropein, hydroxytyrosol, and quercetin as a positive standard in a carbonyl compound (4-hydroxynonenal)-induced model of oxidative damage to rat cardiomyocytes (H9c2). Cell viability was detected by the MTT assay; reactive oxygen species production was assessed by the 2′,7′-dichlorodihydrofluorescein diacetate method, and the mitochondrial membrane potential was determined using a JC-1 dye kit. Phospho-Hsp27 (Ser82), phospho-MAPKAPK-2 (Thr334), phospho-c-Jun (Ser73), cleaved-caspase-3 (cl-CASP3) (Asp175), and phospho-SAPK/JNK (Thr183/Tyr185) were measured by Western blotting. The ethanolic and methanolic extracts of olive leaves inhibited 4-hydroxynonenal-induced apoptosis, characterized by increased reactive oxygen species production, impaired viability (LD50: 25 µM), mitochondrial dysfunction, and activation of pro-apoptotic cl-CASP3. The ethanolic and methanolic extracts of olive leaves also inhibited 4-hydroxynonenal-induced phosphorylation of stress-activated transcription factors, and the effects of extracts on p-SAPK/JNK, p-Hsp27, and p-MAPKAPK-2 were found to be concentration-dependent and comparable with oleuropein, hydroxytyrosol, and quercetin. While the methanolic extract downregulated 4-hydroxynonenal-induced p-MAPKAPK-2 and p-c-Jun more than the ethanolic extract, it exerted a less inhibitory effect than the ethanolic extract on 4-hydroxynonenal-induced p-SAPK/JNK and p-Hsp27. cl-CASP3 and p-Hsp27 were attenuated, especially by quercetin. Experiments showed a predominant reactive oxygen species inhibitory and mitochondrial protecting ability at a concentration of 1–10 µg/mL of each extract, oleuropein, hydroxytyrosol, and quercetin. The ethanolic extract of olive leaves, which contains larger amounts of oleuropein, hydroxytyrosol, verbascoside, luteolin, and quercetin (by HPLC) than the methanolic one, has more protecting ability on cardiomyocyte viability than the methanolic extract or each phenolic compound against 4-hydroxynonenal-induced carbonyl stress and toxicity.
Keywords: Olea europaea L.; Oleaceae; olive leaf extract; cardiomyocytes; 4-hydroxynonenal; oleuropein; hydroxytyrosol; quercetin